Enhancing the interfacial stability of LiNi0.8Co0.15Al0.05O2 cathode materials by a surface-concentration gradient strategy. Issue 40 (22nd September 2021) - Zhou, Xin'an; Zhang, Feilong; Wang, Chao; Fu, Xiaolan; Wang, Bo; Zhao, Dongni; Wang, Peng; Liang, Wenbiao; Li, Shiyou
Abstract : Surface-concentration gradient LiNi0.8 Co0.15 Al0.05 O2 displays better interfacial stability and improved electrochemical performances. Abstract : Ni-rich LiNi0.8 Co0.15 Al0.05 O2 materials have been successfully applied in electric vehicles due to the merits of high energy density which can meet the requirements for driving range. Nevertheless, the electrochemical performances of Ni-rich materials are limited by their structural instability. Herein, LiNi0.8 Co0.15 Al0.05 O2 materials with the concentration-gradient structure of a Ni-rich core and a Co-rich surface were synthesized. The electrochemical results indicate that surface-concentration gradient LiNi0.8 Co0.15 Al0.05 O2 provides improved electrochemical performance. It not only displays an initial Coulomb efficiency of 82.4%, and a capacity retention of 80.37% after 200 cycles at 25 °C, but also shows a capacity retention of 77.76% after 150 cycles at a high temperature of 55 °C. These excellent performances can be attributed to adjusting the distribution of Ni on the surface of the LiNi0.8 Co0.15 Al0.05 O2 material, which inhibits the interfacial reaction between the material surface and electrolyte, lowers the consumption of active Li + and decreases the interfacial film impedance. Moreover, less Ni content on the material surface is beneficial for reducing the formation of a NiO rock salt phase during the charging process and inhibits the surface structural evolution. The proposed method and detected mechanism will provide guidance for the design of cathode materials and their practical industrial applications.